The equation below can be used to find the length of a foot or forearm when you know one or the other. (length of the foot) = 0.
860 • (length of the forearm) + 3.302 If you let y = length of the foot and x = length of the forearm, this equation can be simplified to y = 0.860x + 3.302. Using this equation, how long would the foot of a person be if his forearm was 17 inches long? What is the rate of change of the equation from Part A? Compare the equation from Part A to your data. Are they the same? Which has a greater rate of change? Why do you think the values are different? Is the relation in your data a function? Why or why not? Could the equation in Part A represent a function? Why or why not? Explain your answer.
So, basically: Y=Length of foot X= Length of your forearm. This is simple. Your equation is Y=0.860x + 3.302 So, if you have a forearm (x) that is 17 inches long, then plug in x as 17. This leaves you to evaluate for Y. New equation: Y=0.860(17) +3.302 Work it out, you get: Y=14.62 + 3.302 Work that out, you get: Y= 17.922 inches long. And of course, Y is the foot.
So, your answer: If the forearm is 17 inches long, then the foot is 17.922 inches long. Simple.
So, part 2: Rate of change. Well, you need slope then, because that's the same thing. Y=mx+b, Where m=slope Your answer turns to be 0.860 inches per length of arm, for rate of change.
Skipping the data, as that's only something you'd know.
Yes, it is indeed a function. There can't be any exponents greater than 1 on the placeholder, and it's obviously not a straight line if you plug it in.